The Disk Wind Contribution to the Gamma-Ray Emission from the Nearby Seyfert Galaxy GRS 1734−292 - Nobuyuki Sakai; Tomoya Yamada; Yoshiyuki Inoue; Ellis R. Owen; Tomonari Michiyama; Ryota Tomaru; Yasushi Fukazawa (The Astrophysical Journal)
Radio-quiet Seyfert galaxies have been detected in GeV gamma rays by the Fermi Large Area Telescope (LAT), but the origin of much of this emission is unclear. We consider the nearby example GRS 1734−292, which exhibits weak starburst and jet activities that are insufficient to explain the observed gamma-ray flux. With the first detailed multiwavelength study of this source, we demonstrate that an active galactic nucleus (AGN) disk wind can account for its gamma-ray emission. Using a lepto-hadronic emission model based on a shocked ambient medium and a shocked wind region created by an AGN accretion disk wind, we identify two viable scenarios that are consistent with the Fermi-LAT data and multiwavelength observations: a hadronic pp -dominated scenario and a leptonic external-Compton-dominated scenario. Both of these show that future observations with the Cherenkov Telescope Array and the Southern Wide-field Gamma-ray Observatory could detect TeV emission from a disk wind in GRS 1734−292. Such a detection would substantially improve our understanding of cosmic-ray acceleration efficiency in AGN disk wind systems and would establish radio-quiet Seyfert galaxies as cosmic-ray accelerators capable of reaching ultrahigh energies.